2011
DOI: 10.1111/j.1365-2133.2011.10306.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced intraepidermal nerve fibre density in lesional and nonlesional prurigo nodularis skin as a potential sign of subclinical cutaneous neuropathy

Abstract: Hypoplasia of epidermal sensory nerves independently of clinical parameters is a new finding in PN and suggests involvement of epidermal nerves in PN pathophysiology. To date, it cannot be ruled out that reduced IENF density is due to repeated scratching. However, the presence of hypoplasia in nonlesional PN skin suggests the presence of a subclinical small fibre neuropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
73
3
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(88 citation statements)
references
References 43 publications
7
73
3
5
Order By: Relevance
“…1b), although the increases of nerve density in patients with pruigo nodularis and psoriasis remain unclear. [10][11][12] Similar findings have been observed in animal models, such as nc/nga mice, a model of atopic dermatitis model, 13,14) and in dry skin model mice. 15,16) Such increases in nerve density are also found in the dermis of patients with atopic dermatitis and psoriasis.…”
Section: Histology Of Cutaneous Nerve Fibers In Atopic Dermatitissupporting
confidence: 67%
“…1b), although the increases of nerve density in patients with pruigo nodularis and psoriasis remain unclear. [10][11][12] Similar findings have been observed in animal models, such as nc/nga mice, a model of atopic dermatitis model, 13,14) and in dry skin model mice. 15,16) Such increases in nerve density are also found in the dermis of patients with atopic dermatitis and psoriasis.…”
Section: Histology Of Cutaneous Nerve Fibers In Atopic Dermatitissupporting
confidence: 67%
“…In addition, it was intriguing to note that intraepidermal nerve fiber sprouting was most marked at the periphery, rather than at the center, of nodules. In human prurigo lesions, contradictory results were reported regarding nerve fiber innervation in the epidermis (33,44). These inconsistent results may be explained by the present mouse model demonstrating transitional changes in the intraepidermal nerve fiber density within lesions.…”
Section: Discussioncontrasting
confidence: 50%
“…Recently, it was reported that lesional and uninvolved PN skin biopsies showed significantly decreased intraepidermal nerve fiber density regardless of patient age, origin of PN, intensity or quality of pruritus. 3 However, our data showed nerve fiber elongation in epidermis of PN. This discrepancy may be explained by the difference in different sampling standards and immunostaining methods.…”
contrasting
confidence: 58%